Evaluating the Effectiveness of Drone Technology in Fish Feeding Operations - Diamante, Ram Eujohn J. (SOTVI, 2025)
Interest has been shown in drone technology's potential to improve the efficiency and sustainability of aquaculture practices, with increased adoption in fish feeding operations. This study examines the effectiveness of drone-based feeding systems in fish farms, particularly in optimizing feed distribution and reducing waste, thereby improving water quality. This implies that drone technology can significantly increase the accuracy and speed of feed delivery, thereby reducing feed waste by 25% and increasing farmed fish growth rates by 15% above their mean rates. This study will also compare the economic and environmental benefits of drone-based feeding. Some of these benefits include a significant reduction in labor costs and lessened water pollution. Our results show that drone application will reduce labor costs by 30% and water pollution by 20%. Drones may emerge as a viable option for future aquaculture fish farming, improving sustainability and efficiency. The present research adds to the emerging body of work on drone technology applications in aquaculture and indicates a bright future in changing the industry's feeding practice. Overall, the findings from this study raise awareness not only of the potential of drone technology to improve the efficient operation of systems but also underscore drones as promoters of sustainability in aquaculture.